Mampukah Privatisasi Meningkatkan Efisiensi Perusahaan? Kajian Empiris pada BUMN Sektor Konstruksi - Mahruddin Harahap; Amzul Rifin; Bunasor Sanim (AFRE (Accounting and Financial Review), 2022)
Privatization is one of the Government's efforts to obtain additional capital with one of the goals for the efficiency of BUMN. The efficiency of BUMN due to privatization needs to be studied through data processed using a statistical approach. Based on the results of the study, it can be seen that BUMN is relatively more efficient before privatization compared to after privatization, then it is found that from the tested variables, there are 3 factors that affect the efficiency of construction BUMN, namely total assets, economic growth and interest rate. Privatization has no effect on the efficiency of Construction SOEs. This shows that the privatization carried out has no effect on the company's performance. This can happen because the shares sold to the public are relatively small. The government is still dominant as a shareholder, so management control from the government is still dominant.DOI: https://doi.org/10.26905/afr.v4i2.6234